Práctica docente andragógica y su relación con el rendimiento académico de los estudiantes de la sección nocturna del básico superior de la Unidad Educativa José María Velasco Ibarra del Cantón Buena Fe periodo lectivo 2015-2016. Plan de capacitación. - Mosquera Anchundia, Julio César (2016)
The educational unit José María Velasco Ibarra located in the canton Buena Fe Los Rios Province, is one of the important institutions of this city, and has the task of implementing strategies to overcome student profile with technical vocation and assimilation of scientific knowledge. That is why the andragogical teaching practice is feasible since the institution with 45 years of experience has been a bulwark in the formation of the youth of this part of the country. At present it is important to assess the incidence of andragogical teaching practice in academic performance of students in the night section of the educational unit "José María Velasco Ibarra" because with the new Constitution and laws education changes are occurring, being the most important to optimize the mutual learning of students for this has been chosen as one of the flagship institutions of the province, for its development of productivity with students performing in local companies and outside the province which makes trainers of men and constants and confident women achieve success. This new form of organization allows administrative levels of planning, coordination, management and control, and to promote universal access to quality education and warmth through efficiency and effectiveness. Since andragogic inadequate teaching practice negatively affects the academic performance of students and to this reality, comprehensive education and training of society is essential to the study and analysis of the processes that manages the school. The methodology used to collect information relies on the use of techniques such as surveys, obtaining in the latter, information provided directly by students, teachers and parents, interviews directly with the respective authorities thereof. To solve the problem that arises is derived as proposed andragogic design a training plan that will strengthen the education of students.